Developing Students' Religious Moderation through Group Counseling at Islamic Higher Education - Raja Rahima Munawarah Raja Ahmad; Kasmiati Kasmiati; Nurhayati Zein; Musa Thahir; Zaitun Syahbudin (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2023)
Tolerance in social life is a need for Indonesian citizens. However, cases of intolerance and violence in the name of religion frequently occur in socia life and might influence students at university This research aims to assess the level of religious moderation comprehension among students at UIN (Universitas Islam Negeri/State Islamic University) Suska Riau through group counseling sessions. The study utilized a quantitative approach, employing a descriptive pre-experimental Intack Group Comparison design. The findings revealed that students' understanding of a moderate attitude significantly increased after participating in group counseling on moderation, with a positive score of 97.5% and a negative score of 2.4%. The inclusion of religious moderation as a theme in group counseling positively impacted students' comprehension and attitude towards religious moderation within society. Notably, two indicators, national commitment and tolerance, exhibited the most significant improvements, with respective increases of 35% and 29%. These results suggest that employing group counseling centered around religious moderation can serve as a model for enhancing students' understanding of religious moderation in society.